TIMING, SOURCES AND RATES OF POTASSIUM FERTILIZER APPLICATION FOR POTATO - PAULETTI, Volnei; MENARIM, Emilson (Scientia Agraria, 2004)
With objective to evaluate the effect of different potassium sources, timing and rates for potato (Solanum tuberosum L.), an experiment was established at Pinheirinho farm, Castro county, Parana State Brazil. The experiment was set out in an randomized complete block factorial design, with four replications. Treatments consisted of a factorial combination of two potassium sources (KCl and K2SO4), two timing K application (50% of the application before more 50% during planting and 50% during de planting more 50% during ridge) and four potassium rates (0, 200, 400 and 600 kg of K2O/ha), respectively. The most traditional regional crop, Bintje, was planted 0,75 m by 0,30 m. It was evaluated the leaf nutrient concentration (P, K and Cl at 64 days after the planting), yield, number total tuber, number of big and small tuber, dry matter for big tuber, branch number by plant and plants by plot. The application 50% of before planting more 50% during planting diminished the potato population compared to application of 50% during de planting more 50% during ridge. Regardless potassium source, there was a reduction in the number small tuber in high potassium rate. Crescent KCl use provided increase leaf Cl concentration and decrease total yield and big tubers. Application of potassium sulfate provided higher leaf K concentration than potassium chloride. Inverse relationship between leaf K and Cl concentration and tuber dry matter, diminishing tuber quality.